Development and experimental validation of building systems for masonry housing in seismic areas - Lourenço, Paulo B. (2013)
The evolution of structural masonry is briefly reviewed, from old thrust line behavior to modern global behavior using shear walls. For modern structural masonry, the use of unreinforced, confined and reinforced masonry is addressed in seismic areas. A first focus is given to recent approaches towards the safety assessment of unreinforced masonry buildings and their performance in shaking table tests. Subsequently, building systems for modern masonry structures recently developed and tested at University of Minho are presented, one based on lightweight concrete blocks and another based on normal concrete blocks. The experimental and numerical work carried out is discussed and conclusions on the performance of the systems are given.